2004
DOI: 10.1016/j.jvs.2004.02.031
|View full text |Cite
|
Sign up to set email alerts
|

Perivascular delivery of losartan with surgical fibrin glue prevents neointimal hyperplasia after arterial injury

Abstract: Release of angiotensin II in response to vascular injury may promote neointimal hyperplasia, because this hormone can stimulate smooth muscle cell proliferation and migration. This study demonstrates that local application of an angiotensin receptor antagonist, losartan, to the site of injury can effectively prevent neointimal hyperplasia after balloon angioplasty. Application of losartan to the perivascular surface of the injured vessel in a surgical fibrin glue enabled delivery of a dose that exceeds the max… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
20
0
2

Year Published

2004
2004
2020
2020

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 29 publications
(22 citation statements)
references
References 19 publications
(26 reference statements)
0
20
0
2
Order By: Relevance
“…7) agree with published evidence showing that MT1-MMP expression is induced in vascular tissues by injury (39,48). A recent study (34) from this laboratory has confirmed that MT1-MMP becomes detectable after balloon angioplasty and extended these observations further by showing that expression of MT1-MMP is coupled to activation of the AT 1 receptor. This relationship provides an obvious link between vascular injury and PI3K, because PI3K activation is controlled via the AT 1 receptor (44).…”
Section: Discussionmentioning
confidence: 65%
See 1 more Smart Citation
“…7) agree with published evidence showing that MT1-MMP expression is induced in vascular tissues by injury (39,48). A recent study (34) from this laboratory has confirmed that MT1-MMP becomes detectable after balloon angioplasty and extended these observations further by showing that expression of MT1-MMP is coupled to activation of the AT 1 receptor. This relationship provides an obvious link between vascular injury and PI3K, because PI3K activation is controlled via the AT 1 receptor (44).…”
Section: Discussionmentioning
confidence: 65%
“…Interestingly, expression of MT1-MMP, which is anchored on the cell surface through a transmembrane domain, is also modulated by tissue damage (39,48). Indeed, a correlation between MT1-MMP expression and neotintimal hyperplasia suggests this protein may be involved in the vascular response to injury (34).…”
mentioning
confidence: 99%
“…External fibrin glue support could possibly counteract the intravenous arterial pressure thereby possibly preventing early vein graft overdistension. On the other hand, fibrin application could be used as a vehicle to transport therapeutic agents to prevent intimal hyperplasia at the site of action [14]. In a pig model of neointimal hyperplasia following balloon angioplasty-related endothelial injury, local application of losartan, an inhibitor of the renin-angiotensin system, could reduce neointimal hyperplasia [14].…”
Section: Discussionmentioning
confidence: 99%
“…On the other hand, fibrin application could be used as a vehicle to transport therapeutic agents to prevent intimal hyperplasia at the site of action [14]. In a pig model of neointimal hyperplasia following balloon angioplasty-related endothelial injury, local application of losartan, an inhibitor of the renin-angiotensin system, could reduce neointimal hyperplasia [14]. However, the data deducted from this arterial injury model cannot necessarily be applied to our vein graft model because of the different pathophysiological cause, local endothelial damage due to balloon inflation vs generalized intraluminal pressure increase due to arterialization.…”
Section: Discussionmentioning
confidence: 99%
“…AT1 is the major angiotensin II receptor and is widely expressed in human tissues; AT1 has been shown to mediate vasoconstriction as well as the majority of the physiological and pathophysiological effects of angiotensin II, including cell growth control (for a review see Bader et al 2010). Consequently, AT1 receptor antagonists have been studied as possible therapeutic targets for preventing stenosis (Moon et al 2004). The present study was designed to directly investigate the effect of a selective AT1 receptor antagonist, losartan, on angiotensin II-induced cell proliferation using the rat embryonic thoracic aorta smooth muscle cell line A7r5.…”
Section: Introductionmentioning
confidence: 99%